Comparison of Residents’ Preferences to Liveability Parameters in Different Morphologically Dense Urban Areas - Mangalkar, Mrudula; Raval, Pratap (Calibrating Urban Livability in the Global South, 2024)
Livability is a widely used term in urban environments, but there is no general consensus on precisely defining it. Literature of ‘livability’ suggests a lack of an established assessment framework or a uniform definition; hence, the term can be understood and applied in many ways. Livability is a subjective notion and often linked to various factors such as quality of life, availability of educational and medical facilities, sense of safety, access to infrastructure and basic services, cost and comfort of living, ease of mobility and transit facilities, air quality, and social cohesion. Thus, perception of livability is often seen to be dependent upon how well the built environment caters to the residents’ fundamental needs. The results of various case-based studies carried out in the morphologically dense urban areas, emphasize that this built environment is highly influential to perceived livability. The paper outlines various perspectives of livability and parameters based on literature that are considered for assessing livability at various spatial scales such as global, regional or local level. These literature parameters are assessed through residents’ preferences using focused group discussions, in order to understand the level of importance each of the parameter has in their day-to-day lifestyle and how they find it impacting the livability of their locality, resultant of the varying morphological density. The findings and analysis from this survey shall help understand the people’s perception about those parameters for determining livability of a place in Indian context. This study will not only help for streamlining the knowledge to enhance livability at the local level but also help in understanding how it performs for the users through seeking their preferences with respect to the literature-based parameters of livability. This can help in understanding the performance of these livability parameters in any particular locality due to its morphological density, and thus support existing research and further helping to integrate the same within planning process.